Overlapping Mechanisms of Peripheral Nerve Regeneration and Angiogenesis Following Sciatic Nerve Transection - Wang, Hongkui; Zhu, Hui; Guo, Qi; Qian, Tianmei; Zhang, Ping; Li, Shiying; Xue, Chengbin; Gu, Xiaosong (Frontiers in Cellular Neuroscience, 2017)
Peripheral nervous system (PNS) owns the ability of self-regeneration, mainly in its regenerative microenvironment including vascular network reconstruction. More recently, more attentions have been given to the close relationship between tissue regeneration and angiogenesis. To explore the overlap of molecular mechanisms and key regulation molecules between peripheral nerve regeneration and angiogenesis post peripheral nerve injury, integrative and bioinformatic analysis was carried out for microarray data of proximal stumps after sciatic nerve transection in SD rats. Nerve regeneration and angiogenesis were activated at 1 d immediately after sciatic nerve transection simultaneously. The more obvious changes of transcription regulators and canonical pathways suggested a phase transition between 1 d and 4 d of both nerve regeneration and angiogenesis after sciatic nerve transection. Furthermore, 16 differentially expressed genes participated in significant biological processes of both nerve regeneration and angiogenesis, a few of which were validated by qPCR and immunofluorescent staining. It was demonstrated that STAT3, EPHB3 and Cdc42 co-expressed in Schwann cells and vascular endothelial cells to play a key role in regulation of nerve regeneration and angiogenesis simultaneously response to sciatic nerve transection. We provide a framework for understanding biological processes and precise molecular correlations between peripheral nerve regeneration and angiogenesis after peripheral nerve transection. Our work serves as an experimental basis and a valuable resource to further understand molecular mechanisms that define nerve injury-induced micro-environmental variation for achieving desired peripheral nerve regeneration.